2022
DOI: 10.1007/s00446-021-00418-2
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence classes and conditional hardness in massively parallel computations

Abstract: The Massively Parallel Computation (MPC) model serves as a common abstraction of many modern large-scale data processing frameworks, and has been receiving increasingly more attention over the past few years, especially in the context of classical graph problems. So far, the only way to argue lower bounds for this model is to condition on conjectures about the hardness of some specific problems, such as graph connectivity on promise graphs that are either one cycle or two cycles, usually called the one cycle v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…This has been proven for some special classes of algorithms; for an overview of these results, see [28,Section 3.2]. This conjecture is known to be equivalent to many common combinatorial problems [28]. Specifically, any of the problems that we consider in Section 5.2 need Ω(log n) rounds with strongly sublinear space if this conjecture holds.…”
Section: Massively Parallel Computationmentioning
confidence: 82%
See 1 more Smart Citation
“…This has been proven for some special classes of algorithms; for an overview of these results, see [28,Section 3.2]. This conjecture is known to be equivalent to many common combinatorial problems [28]. Specifically, any of the problems that we consider in Section 5.2 need Ω(log n) rounds with strongly sublinear space if this conjecture holds.…”
Section: Massively Parallel Computationmentioning
confidence: 82%
“…The 1-vs-2-cycles conjecture states that for any > 0, one needs Ω(log n) rounds to tell apart one cycle of length n and two cycles of length n/2 when using n 1−Ω(1) space per machine. This has been proven for some special classes of algorithms; for an overview of these results, see [28,Section 3.2]. This conjecture is known to be equivalent to many common combinatorial problems [28].…”
Section: Massively Parallel Computationmentioning
confidence: 89%
“…One of the notorious problems for low space MPC is the problem of distinguishing whether an input graph is an 𝑛-vertex cycle or two 𝑛 2 -vertex cycles. This fundamental MPC problem has been studied extensively in the literature and has played a central role in the development of conditional lower bounds for MPC graph algorithms (see, e.g., [13,45,52,56]). This problem is trivial for an MPC with local space Ω(𝑛), but we do not know its complexity for low space MPCs.…”
Section: Basic Algorithmic Tools On Low Space Mpcmentioning
confidence: 99%
“…Under the same conjecture, Yaroslavtsev et al [65] showed that single-linkage clustering cannot be approximated by constant factor in o(log n) rounds. Recently, Nanongkai and Scquizzato showed that this conjecture is equivalent to the conjecture that logspace complete problem can not be solved in o(log n) rounds, and consequently, a large class of graph problems, such as single source shortest path, minimum cut, and planarity testing, require asymptotically the same number of rounds under these assumptions [57].…”
Section: Related Workmentioning
confidence: 99%